Fiscal sustainability in an emerging market economy: when does public debt turn bad? - Baharumshah, Ahmad Zubaidi; Soon, Siew Voon; Lau, Evan (Elsevier, 2017)
This paper proposes a Markov-switching model to assess the sustainability of fiscal policy in Malaysia for the period 1980–2014. Our results indicate the policymakers in the past have followed a sustainable fiscal policy, except during the brief periods of economic difficulty. The empirical analysis reveals that the government should cut the deficits only if they exceed a certain level, to ensure their sustainability in the long-run. Specifically, we find that after public debt exceeds a certain threshold level (above 55% of the gross domestic product), it is negatively correlated with economic activity. In addition to the threshold effect, we confirm the presence of a unidirectional causal relation between debt and growth.